RESEARCH OF PHYSICAL AND MECHANICAL INDICATORS OF KNITTED FABRICS MADE OF DIFFERENT RAW MATERIALS - Jurabayev Nozimjon Nizomiddin ugli; Shogofurov Shaxboz Shokirjon ugli; Kholikov Kurbonali Madaminovich (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, 4 samples with high storage properties of modified two-layer form of raw material composition were taken, their technological performance and physical-mechanical properties were studied experimentally, tabulated and analyzed